Hagyományos és automatizált sejtanalitikai módszerek alkalmazása bikaspermiumok kromatinállapotának értékelésére - Kovács, Barnabás Mihály; Kakasi, Balázs; Nagy, Szabolcs Tamás (GEORGIKON FOR AGRICULTURE, 2018)
Recently, evaluations of sperm traits, such as DNA fragmentation, or abnormal condensation of the sperm chromatin, are becoming increasingly important. The aim of the present study was to compare a conventional light microscopic procedure, Feulgen staining, with a modern automated method, the so-called Nicoletti test to evaluate sperm chromatin condensation, and to investigate the relationship between sperm primary defects and chromatin condensation. Our results on the semen samples of 15 Hungarian Simmenthal bulls did not reveal any significant correlation between the two methods. However, there is a significant, strong negative relationship between normal sperm morphology and abnormal chromatin condensation.
Keywords: chromatin condensation; sperm morphology; Feulgen staining; Nicoletti assay